Carboxypeptidase N2 as a Novel Diagnostic and Prognostic Biomarker for Lung Adenocarcinoma - Xu, Ting; Zhang, Zhe; Chen, Hongqiang; Cai, Ruili; Yang, Qian; Liu, Qi; Fan, Yahan; Liu, Wenbin; Yao, Chunyan (Frontiers in Oncology, 2022)
Carboxypeptidase N2 (CPN2) is a plasma metallo-protease that cleaves basic amino acids from the C terminal of peptides and proteins. Emerging evidence showed that carboxypeptidases perform many diverse functions in the body and play key roles in tumorigenesis. However, the clinical significance and biological functions of CPN2 in lung adenocarcinoma remain unclear. Our study aimed to explore the potential role and functions of CPN2 in lung adenocarcinoma. Results showed that the transcription level of CPN2 was significantly increased in tumor tissues of lung adenocarcinoma patients compared to adjacent normal tissues in TCGA cohort (P<0.05). Survival plots showed that the overall survival of patients with high expression of CPN2 was significantly lower than patients with low expression of CPN2, both in Kaplan-Meier database and clinical sample cohort (P<0.05). Tissue microarray analysis found that CPN2 protein expression was significantly positive correlated with node status and tumor stage, as well as the tumor malignancy (P<0.05). Further univariate and multivariate Cox regression analysis showed that CPN2 may act as an independent prognostic factor in patients with lung adenocarcinoma (P<0.05). In addition, co-expression genes analysis from LinkedOmics showed that CPN2 was positively associated with many genes of fibrillar collagen family members and PI3K-Akt pathway. GSEA showed that higher expression of CPN2 may participate in mTOR, TGF-BETA, NOTCH, TOLL-like-receptor, WNT and MAPK signaling pathway in lung adenocarcinoma. Notably, knockdown of CPN2 significantly inhibited the ability of cell proliferation, clone formation, invasion and migration. Our findings suggested that up-regulation of CPN2 is associated with worse clinical outcome in lung adenocarcinoma and cancer-related pathways, which laid the foundation for further research of CPN2 during carcinogenesis.